Legality as Reason: Dicey, Rand, and the Rule of Law - Walters, Mark (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2010)
For many law students in Canada, the idea of the rule of law is associated with the names of Professor A.V. Dicey, Justice Ivan Rand, and the case of Roncarelli v. Duplessis. It is common for students to read excerpts from Dicey’s Law of the Constitution on the rule of law, and then to examine how the rule of law is, as Rand stated in Roncarelli, “a fundamental postulate of our constitutional structure.” Indeed, Roncarelli marked a point in time, fifty years ago, at which the academic expression “the rule of law” became a meaningful part of the legal discourse of judges and lawyers in Canada.In this article, the author considers the relationship between the rule of law as an academic or conceptual idea and the rule of law as a practical or doctrinal idea. A distinction is drawn between two traditions of theorizing about the rule of law, which are labelled “legality as order” and “legality as reason”. The author then reconsiders the views of both Dicey and Rand and argues that both advanced the idea of legality as reason. The author concludes that, although Canadian judges now tend to emphasize legality as order, we are better placed to understand the special features of constitutionalism in Canada if we remember that the rule of law has, both conceptually and doctrinally, another dimension—that which is associated with the idea of “legality as reason”.